Magnitude and risk factors of khat, alcohol and cigarettes use among pregnant women in Africa: a systematic review and meta-analysis - Biruk Wogayehu; Tsegaye Demissie; Mekuriaw Alemayehu; Eskinder Wolka; Kassa Daka (BMC, 2024)
Abstract Background The use of khat, alcohol, and cigarettes during pregnancy is a serious public health problem associated with harmful outcomes for the fetus and the mother's health. Studies that investigated khat, alcohol, and cigarettes usage during pregnancy yielded varied and contradictory results. This study used a systematic review and meta-analysis to estimate the pooled prevalence and associated factors of khat, alcohol, and cigarettes use among pregnant women in Africa. Methods A review of eligible studies was conducted using Preferred Reporting Items for Systematic Reviews and Meta-Analysis (PRISMA) guidelines. This review has been registered in PROSPERO with protocol ID CRD42021289074. Literature published in English from January 1, 2002 to November 30, 2021 was retrieved from PubMed, Google Scholar, Cochrane, HINARI, African Journal Online, and Science Direct databases. The quality of included articles was assessed using the Joanna Briggs Institute's (JBI) critical appraisal checklist. The I2 statistic and Cochran's Q test were used to assess the presence of heterogeneity between studies. To assess publication bias, a funnel plot and Egger's regression test were utilized. The random effect model was used to estimate the summary prevalence and the corresponding 95% confidence interval (CI) of risk factors for khat, alcohol, and cigarettes use. Results Out of the 1509 studies identified, 71 met the inclusion criteria. The pooled prevalence of khat chewing, alcohol drinking, active smoking, and secondhand smoke exposure during pregnancy was 18.93%, 22.20%, 11.85%, and 43.45%, respectively. The subgroup analysis by UN sub-region showed the highest pooled prevalence of alcohol use during pregnancy in Middle Africa (25.69%) and the lowest in Northern Africa (1.10%). Several factors were identified as risk factors for alcohol use, including low educational level, younger age women, pre-pregnancy alcohol use, unplanned pregnancy, history of abortion, poor social support, mental distress, poor knowledge on alcohol risks, and partner alcohol use. Conclusion This review indicated that the pooled magnitude of khat, alcohol and cigarette use during pregnancy was higher in Africa. Substance use screening and brief interventions (SBI) should be routinely delivered in antenatal care settings to reduce pregnant women's substance use.